Mirtazapine Treatment of a Severe Depressive Episode and Resolution of Elevated Inflammatory Markers. (9th October 2013) - Alikhan, Shahzad M.; Lee, Jessica A.; Dratcu, Luiz
Abstract : Depression has been shown to be associated with systemic inflammatory activity and the mode of action of several antidepressants appears to involve immunomodulation. Effects on immune system activity have also recently been observed in correlation with therapeutic response to mirtazapine in cardiac patients with depression, but no study has yet examined these effects in otherwise physically healthy depressed patients treated with mirtazapine. This report describes an association between a clinical antidepressant response and a decrease in markers of systemic inflammation observed during pharmacotherapy with mirtazapine in a severely depressed but physically well patient. This observation adds to the evidence that changes in inflammatory responses may be implicated in the mode of action of antidepressants. Further studies of antidepressant responses to mirtazapine and levels of inflammatory markers in depressed patients without medical comorbidity can help elucidate the role of the immune system in the pathophysiology of depression, and hence contribute to the development of novel antidepressant therapies.